Urinary shedding of common DNA viruses and their possible association with bladder cancer: a qPCR-based study - Hrbáček, Jan; Hanáček, Vítězslav; Kadlečková, Dominika; Cirbusová, Adéla; Čermák, Pavel; Tachezy, Ruth; Zachoval, Roman; Saláková, Martina (Neoplasma, 2023)
After a decade of human urinary microbiota research, little is known about the composition of the urinary virome and its association with health and disease. This study aimed to investigate the presence of 10 common DNA viruses in human urine and their putative association with bladder cancer (BC). Catheterized urine samples were collected from patients undergoing endoscopic urological procedures under anesthesia. After DNA extraction from the samples, viral DNA sequences were detected using real-time PCR. Viruria rates were compared between BC patients and controls. A total of 106 patients (89 males and 17 females) were included in the study. Fifty-seven (53.8%) were BC patients and 49 (46.2%) had upper urinary tract stones or bladder outlet obstruction. The viruses detected in the urine were human cytomegalovirus (2.0%), Epstein-Barr virus (6.0%), human herpesvirus-6 (12.5%), human papillomavirus (15.2%), BK polyomavirus (15.5%), torque teno virus (44.2%), and JC polyomavirus (47.6%), while no adenoviruses, herpes simplex virus 1 and 2, or parvoviruses were found. There were statistically significant differences in HPV viruria rates between cancer patients and controls (24.5% vs. 4.3%, p=0.032 after adjustment for age and gender). Viruria rates increased from benign to non-muscle-invasive and muscle-invasive tumors. Patients with a history of BC have higher HPV viruria rates than controls. Whether this relationship is a causal one remains to be established by further research.
Keywords: Epstein-Barr Virus Infections; virus Epsteinův-Barrové; lidé; Female; Papillomavirus Infections; mužské pohlaví; infekce virem Epsteina-Barrové; Male; Herpesvirus 4, Human; Urinary Bladder Neoplasms; DNA Viruses; DNA viry; nádory močového měchýře; ženské pohlaví; infekce papilomavirem; Humans